The Astonishing Diversity of Ig Classes and B Cell Repertoires in Teleost Fish - Fillatreau, Simon; Six, Adrien; Magadan, Susanna; Castro, Rosario; Sunyer, J. Oriol; Boudinot, Pierre (Frontiers in Immunology, 2013)
With lympoid tissue anatomy different than mammals, and diverse adaptations to all aquatic environments, fish constitute a fascinating group of vertebrate to study the biology of B cell repertoires in a comparative perspective. Fish B lymphocytes express immunoglobulin (Ig) on their surface and secrete antigen-specific antibodies in response to immune challenges. Three antibody classes have been identified in fish, namely IgM, IgD and IgT, while IgG, IgA and IgE are absent. IgM and IgD have been found in all fish species analyzed, and thus seem to be primordial antibody classes. IgM and IgD are normally co-expressed from the same mRNA through alternative splicing, as in mammals. Tetrameric IgM is the main antibody class found in serum. Some species of fish also have IgT, which seems to exist only in fish and is specialized in mucosal immunity. IgM/IgD and IgT are expressed by two different sub-populations of B cells. The tools available to investigate B cell responses at the cellular level in fish are limited, but the progress of fish genomics has started to unravel a rich diversity of IgH and IgL locus organization, which might be related to the succcession of genome remodellings that occured during fish evolution. Moreover, the development of deep sequencing techniques has allowed the investigation of the global features of the expressed fish B cell repertoires in zebrafish and rainbow trout, in steady state or after infection. This review provides a description of the organization of fish Ig loci, with a particular emphasis on their heterogeneity between species, and presents recent data on the structure of the expressed Ig repertoire in healthy and infected fish.